Digitalisasi Pelayanan Administrasi Kependudukan di Desa Taunbaen Timur Berbasis Website Menggunakan Metode Prototype - Dionisius K. Amsikan; Yoseph P. K. Kelen; Krisantus Tey Seran (Mulawarman University, 2023)
One of the main tasks of a village office is the population administration handling and permit paperwork service. The village population administration handling at East Tuanbaun Village, the sub-district of North Biboki, the District of North Central Timor up to the current time, is still implemented conventionally. The data processing management, such as letter of recommendations, document filing are still conventionally recorded in books. Such conditions are considered very ineffective and undeniably very time consuming, particularly when someone is trying to find data. Apart from that it is very lackadaisical and results in long queue whenever people come to get their paper work done. We, in this research, develop website-based information system for population administration service named SIADES. This website platform is chosen as it can be easily and freely accessed from any place at anytime. This application is developed using prototype method, providing the system development method can give access to the interaction between the user and the developer. The existence of this application can help the village officers and the society in handling letters of permit. People don't have to come to the village office to get their permit/recommendation letter since they can do it using online website service. On top of that, all the digitally saved data will remain safe and long-lasting.